The effect of braid angle on the flexural performance of structural braided thermoplastic composite beams. (1st April 2021) - Singh, Anubhav; Reynolds, Neil; Keating, Elspeth M.; Barnett, Alastair E.; Barbour, Steve K.; Hughes, Darren J.
Highlights: Flexural behaviour of braided beams with different braid angles was investigated. Advanced characterisation techniques were used to analyse the deformation of beams. Two deformation modes were observed: global flexure and localised crush. The extent of localised crushing reduced with increasing braid angle. Stiffness and peak load showed a positive correlation with braid angle. Abstract: Thermoplastic braided composite tubular beams were manufactured using commingled hybrid yarn with braid angles 30°, 45° and 60° and tested in static three-point flexure. Two principal deformation modes were observed during the flexural loading: global flexure and localised crush. The extent of each mode occurring in the three braid angle variants was measured using a linear deflectometer as well as 3D digital image correlation. Localised crushing was found to decrease significantly with increasing braided angle, accounting for 63%, 45% and 19% of the total applied deflection for the 30°, 45° and 60° beams respectively. Further, surface strain measurements obtained from 3D DIC showed increasing the braid angle led to a global flexure-dominated deformation. In addition, the stiffness and peak load increased with increasing braid angle. The observed differences in deformation modes were due to a combination of multiple braid angle-dependent properties of braided composites such as modulus, thickness etc.